International Network for the Availability of Scientific Publications - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
IINASPAccess to current scientific and technical literature is essential to research and teaching. In many countries, universities and research institutes cannot fulfill their mandate because lack of foreign currency and other problems make it...